Domestic Help - Lai, Florence Kit Wah (2012)
Domestic Help is a short film produced by four final year students of the Wee Kim Wee School of Communication and Information, as their Final Year Project (FYP). It touches on the social issue of foreign domestic helpers and their plight in Singapore. The project took about nine months to complete, under the supervision of Associate Professor Adam Knee and Mr Kym Campbell. This FYP report aims to document the process of this 15-minute short film, from conceptualization to the post-production stages of producing the film. It will also document our personal reflections on this challenging journey in filmmaking and the lessons we took away from this project.